2021
DOI: 10.21037/tp-21-399
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum sealing drainage combined with free anterolateral femoral skin flap grafting in 16 cases of pediatric soft tissue damage to the foot and ankle

Abstract: Background: To investigate the clinical experience and discuss the use of vacuum sealing drainage (VSD) combined with free anterolateral femoral flap grafting to treat pediatric foot and ankle soft tissue traumas.Methods: This was a retrospective analysis of 16 pediatric patients with foot and ankle soft tissue traumas treated with free anterolateral femoral flap grafting from January 2015 to January 2018. After successful debridement and VSD, the clinical efficacy of the procedure was evaluated by observing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…With the wide application of VSD technology in clinical practice, it has been proved to have high clinical efficacy in the treatment of diabetic foot, ulcer wounds, etc. Numerous studies have shown that VSD can not only remove exudates and necrotic tissue in wounds in time but also reduce the infection rate to a certain extent [9].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…With the wide application of VSD technology in clinical practice, it has been proved to have high clinical efficacy in the treatment of diabetic foot, ulcer wounds, etc. Numerous studies have shown that VSD can not only remove exudates and necrotic tissue in wounds in time but also reduce the infection rate to a certain extent [9].…”
Section: Related Workmentioning
confidence: 99%
“…With the wide application of VSD technology in clinical practice, it has been proved to have high clinical efficacy in the treatment of diabetic foot, ulcer wounds, etc. Numerous studies have shown that VSD can not only remove exudates and necrotic tissue in wounds in time but also reduce the infection rate to a certain extent [ 9 ]. The DAT structure has a variety of growth factors such as collagen, glycosaminoglycan, and VEGF, which can be used as a three-dimensional scaffold material to promote tissue regeneration.…”
Section: Related Workmentioning
confidence: 99%
“…Several studies have shown that VSD technique has a promising performance in treating wound beds infected with various pathogenic microorganisms [5] , [6] . The adjuvant treatment of VSD may help to cover the dead space, reduce wound healing time and the risk of recurrent infection [7] . As the initial measures of wound care, serial debridement and STS treatment have not slowed down the progress of the disease in this case, the VSD along with the creative use of topical antibiotic flushing provided the best solution to promote healing of the infected field within 12 weeks in this case.…”
Section: Discussionmentioning
confidence: 99%
“…e approach of VSD is outside the sphincter or at the sphincter tendon, reducing the damage to the sphincter during surgery and protecting the anal function to the greatest extent. Continuous negative pressure can collapse the abscess cavity, which is beneficial to the closure of the abscess cavity and the healing of the wound, reducing the length of hospital stay and promoting early recovery of patients [23]. Xue et al [24] explored the therapeutic effect of VSD on wound repair time and inflammation in patients with soft tissue trauma compared with the traditional treatment.…”
Section: Discussionmentioning
confidence: 99%